2018
DOI: 10.1177/0300060518776064
|View full text |Cite
|
Sign up to set email alerts
|

Role of probiotics in the treatment of minimal hepatic encephalopathy in patients with HBV-induced liver cirrhosis

Abstract: ObjectiveThis study was performed to investigate the role of probiotics (Clostridium butyricum combined with Bifidobacterium infantis) in the treatment of minimal hepatic encephalopathy (MHE) in patients with hepatitis B virus (HBV)-induced liver cirrhosis.MethodsSixty-seven consecutive patients with HBV-induced cirrhosis without overt hepatic encephalopathy were screened using the number connection test and digit symbol test. The patients were randomized to receive probiotics (n = 30) or no probiotics (n = 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 32 publications
2
73
0
1
Order By: Relevance
“…Hepatic encephalopathy is closely related to the intestinal microbiota (162). The metabolic activity of the intestinal microbiota on amino-acids results in the production of toxic substances (NH3, phenols, amines, phenolic acids) that are inactivated in the liver.…”
Section: Liver Diseases and Hepatic Encephalopathymentioning
confidence: 99%
“…Hepatic encephalopathy is closely related to the intestinal microbiota (162). The metabolic activity of the intestinal microbiota on amino-acids results in the production of toxic substances (NH3, phenols, amines, phenolic acids) that are inactivated in the liver.…”
Section: Liver Diseases and Hepatic Encephalopathymentioning
confidence: 99%
“…Bacterial Genomic DNA Extraction. Fecal genomic DNA was extracted using a QIAamp® DNA Stool Mini Kit (QIAGEN, Hilden, Germany) according to our previous studies [4,19]. The amount of bacterial genomic DNA was analyzed using a NanoDrop ND-1000 spectrophotometer; the integrity and size of bacterial genomic DNA were checked by electrophoresis.…”
Section: Subjects' Selectionmentioning
confidence: 99%
“…For fecal abundant bacteria analysis, real-time quantitative PCR (qPCR) was performed on ABI Prism 7900HT real-time PCR system (Applied Biosystems, Carlsbad, CA) with a Power SYBR Green PCR Master Mix (Takara, Dalian, China) according to the manufacturer's instructions. The bacterial primer sets and the reaction conditions are shown in Table 2 [19,20]. SDS 2.4 was used for the data analysis.…”
Section: Fecal Abundant Bacteria Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal barrier was improved after the probiotics treatment, resulting in a decreased level of venous ammonia and increased cognitive ability in patients with liver cirrhosis. 141 Accordingly, Dhiman et al 142 have found that the VSL#3 treatment in patients with liver cirrhosis reduces the risk of hospitalization for hepatic encephalopathy and decreases the severity of cirrhosis.…”
Section: Targeting Gut Microbiota For Hcc Preventionmentioning
confidence: 99%